Seawater carbonate chemistry and survival of different members in Antarctic macroalgal-associated amphipod assemblages - Oswalt, Hannah E; Schram, Julie B; Amsler, Margaret O; Amsler, Charles D; McClintock, James B (PANGAEA, 2025)
To assess how long-term acidification may influence the survival of different members in Antarctic macroalgal-associated amphipod assemblages, mesograzers, particularly amphipods, associated with the brown alga Desmarestia menziesii were collected from the immediate vicinity of Palmer Station, Antarctica (S64°46′, W64°03′) in January 2020 and maintained under three different pH treatments simulating ambient conditions (approximately pH 8.1), near-future conditions for 2100 (pH 7.7), and distant future conditions (pH 7.3) for 52 days then enumerated. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from U.S. Antarctic Program Data Center (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-07-02.
Keywords: Antarctic; Benthos; Bottles or small containers/Aquaria (<20 L); Coast and continental shelf; Community composition and diversity; Desmarestia menziesii; Entire community; Laboratory experiment; Polar; Rocky-shore community